Influences of Graphene Oxide on Mechanical Properties and Mesoscopic Deformation and Failure Process of Concrete - Hong Gong; Xiangxiang Yin; Yi Zhang; Wei Wang; Zongjie Chen (Advances in Civil Engineering)
In this research, graphene oxide (GO) was integrated into concrete to assess its effectiveness as an additive. Triaxial compression permeability experiments, variable-angle (30°, 45°, and 60°) shear experiments, and dynamic compression experiments were conducted on graphene oxide concrete (GOC) and normal concrete (NC). The Holmquist–Johnson–Cook model and LS-DYNA software were utilized to simulate the mesoscopic failure of NC and GOC under impact loading. The mechanism of GO was examined through scanning electron microscope (SEM) microscopic scanning and energy dispersive spectroscopy (EDS) energy spectrum testing. The findings demonstrate that the contain of GO significantly enhances the destruction resistance of concrete under triaxial compression. The permeability of both NC and GOC exhibits a negative exponential decrease with increasing confining pressure, and carbon fiber reduces concrete permeability by 17.79%–60.9%. Compared to NC, the cohesion and internal friction angle of GOC increased by 7.80% and 8.55%, respectively. GO also improves energy conversion and storage capacity during the elastic stage of concrete, reducing inelastic energy loss during shear processes. Although, both NC and GOC exhibit strain rate sensitivity, the DIF value of GOC surpasses that of NC and the disparity between the two intensifies with increasing impact pressure. Simulation results indicate that the number of crushing units in GOC is significantly lower than in NC, maintaining integrity. Analysis of SEM microscopic test results reveals that the distribution of cement hydration products in NC is uniform, whereas in GOC, it displays regional characteristics, a phenomenon corroborated by EDS energy spectrum test results.